How do higher education institutions promote sustainable development? A literature review. (23rd June 2021) - Berchin, Issa Ibrahim; de Aguiar Dutra, Ana Regina; Guerra, José Baltazar Salgueirinho Osório de Andrade
Abstract: Higher education institutions (HEIs) have a fundamental role in transforming societies aimed at a more sustainable future. Through knowledge creation and dissemination, research, education and outreach, institutions of higher education lead the path towards sustainable development. The aim of this paper is to identify, based on a review of the literature, how HEIs promote sustainable development. An analysis of both international declarations and the scientific literature on education for sustainable development shows that emphasis is given to discussions on development, education, research, and training. This highlights the need for a stronger role of universities to promote sustainable development paths, expanding and disseminating knowledge, building capacity through training, and working with local communities to increase their resilience.